2010
DOI: 10.1162/jocn.2009.21303
|View full text |Cite
|
Sign up to set email alerts
|

Coercion and Compositionality

Abstract: Abstract■ Research in psycholinguistics and in the cognitive neuroscience of language has suggested that semantic and syntactic processing are associated with different neurophysiologic correlates, such as the N400 and the P600 in the ERPs. However, only a handful of studies have investigated the neural basis of the syntax-semantics interface, and even fewer experiments have dealt with the cases in which semantic composition can proceed independently of the syntax. Here we looked into one such casecomplement c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 48 publications
(71 reference statements)
7
54
2
Order By: Relevance
“…However, a number of previous studies using sentence contexts have reported N400 effects of semantic integration difficulty when cloze probability was relatively well-matched [23,24,25,26,67,68,69]. Although in each individual case one might argue that predictability or association was not perfectly controlled, taken together the results lend support to the idea that integration difficulty does modulate the N400 to some extent.…”
Section: Discussionsupporting
confidence: 61%
“…However, a number of previous studies using sentence contexts have reported N400 effects of semantic integration difficulty when cloze probability was relatively well-matched [23,24,25,26,67,68,69]. Although in each individual case one might argue that predictability or association was not perfectly controlled, taken together the results lend support to the idea that integration difficulty does modulate the N400 to some extent.…”
Section: Discussionsupporting
confidence: 61%
“…Perhaps the observed effect is more sustained because the processes that are involved in defeasible reasoning are more demanding than in a "discourse-N400" paradigm. In a recent study, Baggio, Choma, van Lambalgen, and Hagoort (2010) found a similar sustained central negativity for coercion verbs such as to begin in "The journalist began the article before his coffee break" compared to "The journalist wrote the article before his coffee break." The first sentence requires the reader to infer what is actually meant by began.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, coercion verbs involve some semantic enrichment, which seems to require additional processing. Baggio et al (2010) suggest that the sustained central negativity-or "N400-like shift"-they observed may be associated with more complex, inference-driven integration of information into a semantic representation. In a similar way, the observed sustained negativity in the present study could also reflect more complex, inference-driven interpretive processes, resulting in a sustained N400-like effect.…”
Section: Discussionmentioning
confidence: 90%
“…Psycholinguistic studies, using a variety of experimental paradigms, report that combining an entity-denoting complement with a coercion verb (John began the book) engenders more processing cost than combining it with a non-coercion verb (John read/wrote the book) during real-time comprehension (Baggio et al 2010;Frisson and McElree 2008;Katsika et al 2012;Lapata et al 2003;McElree et al 2001McElree et al , 2006Pickering et al 2005Pickering et al , 2006Scheepers et al 2004Scheepers et al , 2008Traxler et al 2002Traxler et al , 2005. On the neurolinguistic side, it has been found that the complement coercion effect recruits three distinct cortical regions: Wernicke's area (Piñango et al 2001), ventro-medial 1 The term coercion is widely used to describe diverse phenomena in which it appears that interpretations are derived despite apparent semantic incongruity or mismatch between the combining expressions.…”
Section: The Complement Coercion Phenomenonmentioning
confidence: 99%